Kinerja Pegawai dilihat dari Pendidikan, Pengalaman Kerja, dan Etos Kerja - Marlius, Doni; Anwar, Saiful; Putra, Reynald Yudissa (JURNAL PUNDI, 2024)
This study aims to obtain tested explanative findings about (1) The effect of education on employee performance, (2) The effect of Work Experience on Employee Performance, (3) The Effect of Work Ethic on Employee performance on Batur KPN. The research design used in this study is quantitative. The subjects in this study were all Batur KPN Employees, and the object of research was education, work experience, work ethics and employee performance. The population in this study amounted to 75 employees. All of these populations were made into observation units, so this study was included as population research. Data collected in this study are education data, work experience, work ethics and employee performance sourced from employees and Chair of KPN Batur. Data collection techniques in this study were (1) questionnaire, and (2) ument recording, then analyzed using multiple regression analysis. The results showed a positive effect of (1) education on employee performance, (2) work experience on employee performance, (3) work ethic on employee performance at Batur KPN